2002
DOI: 10.1103/physrevb.66.155310
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot origin of luminescence in InGaN-GaN structures

Abstract: We report on resonant photoluminescence ͑PL͒ of InGaN inclusions in a GaN matrix. The structures were grown on sapphire substrates using metal-organic chemical vapor deposition. Nonresonant pulsed excitation results in a broad PL peak, while resonant excitation into the nonresonant PL intensity maximum results in an evolution of a sharp resonant PL peak, having a spectral shape defined by the excitation laser pulse and a radiative decay time close to that revealed for PL under nonresonant excitation. Observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 34 publications
2
64
1
Order By: Relevance
“…4(b). The PL decay trace from the side QW is nonexponential, in agreement with previous measurements, 12 and exhibits a fast initial decay followed by a slower component. The trace from the QD closely matches that observed from the side well in both shape and lifetime.…”
supporting
confidence: 78%
“…4(b). The PL decay trace from the side QW is nonexponential, in agreement with previous measurements, 12 and exhibits a fast initial decay followed by a slower component. The trace from the QD closely matches that observed from the side well in both shape and lifetime.…”
supporting
confidence: 78%
“…In order to confirm our presumption regarding the QD nature of the InGaN/GaN structures on Si, we performed resonant TR PL investigations in a manner similar to that reported for InGaN/GaN multilayers on sapphire [16]. As mentioned above, the continuous function of density of states of QWs leads to fast carrier relaxation into states of minimal energy after resonant excitation significantly above the PL onset.…”
Section: Time Resolved Studies On Quantum Dot Ensemblesmentioning
confidence: 99%
“…6,[20][21][22][23][24][25] It has been found that the internal quantum efficiency can be enhanced by nanoscale islands or quantum dots observed in AlGaN. 6,20,24 Moreover, atomic-scale compositional superlattice (SL) has also been observed in Al-rich AlGaN thin films grown by molecular-beam epitaxy.…”
Section: Introductionmentioning
confidence: 99%